Public support for unhealthy food marketing policies in Australia: A cross-sectional analysis of the International Food Policy Study 2022 - Clara Gomez-Donoso; Bridget Kelly; Florentine Martino; Adrian J. Cameron; Ana Paula C. Richter; Gary Sacks; Lana Vanderlee; Christine M. White; David Hammond; Kathryn Backholer (Australian and New Zealand Journal of Public Health)
Objective: This study aimed to explore public opinion towards food marketing policies. Methods: In 2022, a cross-sectional online survey was completed by 3,923 adults in Australia, including 1,152 caregivers of children aged <18 years. Concern about children’s exposure to unhealthy food marketing was assessed among caregivers. Public support for seven policy options to restrict unhealthy food marketing in different media and settings (broadcast, online, outdoors, packaging and retail) was quantified. Multivariable regression analyses were conducted to examine sociodemographic differences. Results: Most caregivers (85%) reported some degree of concern about their child’s exposure to unhealthy food marketing. Among all respondents, there was a high level of support or neutrality (>70%) for all policies aimed at restricting unhealthy food marketing. Respondents who were female, older, highly educated, who identified as Aboriginal and/or Torres Strait Islander, perceived their monthly income as adequate or had at least one child living in the household reported higher support/neutrality towards several of the assessed policies. Conclusions: Most Australian adults were supportive or neutral towards policies restricting unhealthy food marketing. The level of support varied depending on the policy’s target group and its setting. Implications for Public Health: Implementing unhealthy food marketing policies in Australia would most likely have broad public support and minimal opposition.